2021
DOI: 10.1080/02255189.2021.1890003
|View full text |Cite
|
Sign up to set email alerts
|

Pandemic, informality, and vulnerability: impact of COVID-19 on livelihoods in India

Abstract: We greatly acknowledge their efforts in the project and several others who provided their valuable feedback at numerous stages of the project. We are particularly grateful to Deepti Goel, Arjun Jayadev, Rajendran Narayanan, and Anand Srivastava for several discussions and for their comments and feedback. We acknowledge Azim Premji University and the Azim Premji Philanthropic Initiatives for their support and funding for the project. We are thankful to the staff at the various civil society organizations who co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
125
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(133 citation statements)
references
References 18 publications
8
125
0
Order By: Relevance
“…In Ceballos et al, (2020) phone survey in Harayana and Odisha, households reported inability to access or afford sufficient quantity and variety of foods. Kesar et al (2020) phone survey of 12 states, 75% of respondents reported consuming less food than before the lockdown, and 35% not having enough money to buy a week's worth of essential goods like food, water, and healthcare. Acharya (2020) phone study concludes that between 50 and 60% of households in the different states faced shortages of food items (mostly nonstaples such as fresh foods and vegetables) in the 30 days preceding the survey and reduced food intake during the lockdown.…”
Section: Data Methods and Measurementmentioning
confidence: 99%
See 2 more Smart Citations
“…In Ceballos et al, (2020) phone survey in Harayana and Odisha, households reported inability to access or afford sufficient quantity and variety of foods. Kesar et al (2020) phone survey of 12 states, 75% of respondents reported consuming less food than before the lockdown, and 35% not having enough money to buy a week's worth of essential goods like food, water, and healthcare. Acharya (2020) phone study concludes that between 50 and 60% of households in the different states faced shortages of food items (mostly nonstaples such as fresh foods and vegetables) in the 30 days preceding the survey and reduced food intake during the lockdown.…”
Section: Data Methods and Measurementmentioning
confidence: 99%
“…Acharya (2020) phone study concludes that between 50 and 60% of households in the different states faced shortages of food items (mostly nonstaples such as fresh foods and vegetables) in the 30 days preceding the survey and reduced food intake during the lockdown. The limitations of previous studies using telephone surveys were that they (a) were primarily qualitative using self-reported measures to determine food security outcomes (Acharya, 2020;Ceballos et al, 2020;Kesar et al, 2020); (b) the survey data collected were cross-sectional, without a reliable baseline for comparison and assess the extent of change first; (c) they did not distinguish between to access and consumption of staples and nonstaples separately and (d) except for Acharya (2020), focused on the household at large not accounting for intrahousehold food allocation or the disproportionate effect on women. The following section details the study's location, data collection, analytical framework, validation, and measurement.…”
Section: Data Methods and Measurementmentioning
confidence: 99%
See 1 more Smart Citation
“…In India, a survey conducted in April 2020, shortly after the implementation of lockdown measures, shows that women were more likely than men to report additional child and elderly care responsibilities (South Asia Gender Innovation Lab 2020). Another study for India shows that women who lost their jobs in the initial phase of the pandemic were more likely than men to report themselves as being engaged in domestic activities, and less likely to actively seek employment (Kesar et al 2021). Some of the cross-country studies further show that the presence of school-age children in the household is empirically correlated with the loss of employment by women.…”
Section: Time Use Care and Impacts On Workmentioning
confidence: 99%
“…This has resulted in serious economic problems for many countries, including the Arab Gulf states, which have suffered due to the lower demand for oil. As pointed out by Kesar, et al [5], the coronavirus pandemic has resulted in a large-scale humanitarian crisis leading to misery and suffering for all of humanity, and pushing social and economic well-being to the brink of collapse.…”
Section: Introductionmentioning
confidence: 99%